Neuroprotective effect of huperzine-A against cadmium chloride-induced Huntington's disease in Drosophila melanogaster model - Mamangam Subaraja; Selvaraj Arokiyaraj; Pratheesh Mathew (Journal of King Saud University: Science, 2024)
Objectives: Huntington's disease is an incurable neurodegenerative disease caused by a huntingtin gene defect; it causes changes in the brain, which affect movement and mental functions. The molecular mechanism still challenges the research to find the treatment of Huntington's disease. The present study aims to develop the neuroprotective potential of huperzine-A against Huntington's disease through in-silico, in-vivo, and in-vitro approaches. Methods: The preliminary screening of the huperzine-A, linalool, norsanguinine, tumerone, ungeremine, tetrabenazine, and astragalin ligands that interact with neuropathological proteins was performed by Auto Dock. In further studies, the biochemical and m-RNA levels of huperzine-A against cadmium chloride-induced in-vitro and in-vivo models were carried out. Results: The interaction of huperzine-A with huntingtin has shown a binding energy of −7.85 kcal/mol. The level of wnt3a and CAMK2A were significantly increased (*p ≥ 0.05), and superoxide dismutase and catalase activities were significantly reduced (*p ≥ 0.05) in cadmium chloride-treated SH-SY5Y cells when compared to that of the control group. The dopamine and serotonin levels were significantly increased (*p ≥ 0.05), and the neuronal behavior pattern was significantly altered in the cadmium chloride-induced group compared to control flies. Conclusions: These results indicate the neuroprotective effect of huperzine-A against cadmium chloride-induced degeneration in Drosophila melanogaster and huperzine-A could minimize neurodegenerative symptoms like − Huntington's disease.